Complications of diabetes in China: health system and economic implications - Wenhui Mao; Chi-Man Winnie Yip; Wen Chen (BMC, 2019)
Abstract Background The prevalence of diabetes and diabetic complications increased alarmingly which also brought heavy burden to patients and health system. Methods We used mix approaches to summarize evidence from published articles and policy documents on the extent and trends of diabetic complications, potential causes, and awareness and services utilization of diabetes in China. Results The annual direct medical expense per patient varied among different types of complications and increased dramatically with the number of diabetic complication and patients were exposed to great financial risk. The number of health policies and strategies on diabetes and its complications at the national level is limited. Primary and secondary preventions such as health education and early diagnosis are necessary. Conclusions With an increasingly burden of non-communicable diseases such as diabetes and its complications, efforts should be invested in education, early screening mechanism and patient management programs to improve the primary and secondary prevention of diabetes and its complications. An integrated services delivery system centered on primary level is recommended to promote education, early case-detection and screening, patient management, referral and care-coordination between primary, secondary and tertiary health care providers.